2010
DOI: 10.1080/09540101003596644
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glycinin and β-conglycinin on enterocyte apoptosis, proliferation and migration of piglets

Abstract: Glycinin and b-conglycinin have been identified as major food/feed allergens. But effects of glycinin and b-conglycinin on enterocyte migration in piglets are scare. Fifteen weanling (7.0690.18 kg) General No. 1 barrows, weaned at 28 days, were used. The piglets were randomly allotted to three (A, B and C) treatments with five replicates. The piglets in the A group (control group) were fed diets without ingredients originating from leguminous products, while the piglets in the B or C groups were fed the diets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 20 publications
5
34
0
Order By: Relevance
“…In addition, FE and PE were significantly decreased by 40–80 g/kg dietary β‐conglycinin. These findings were supported by the results in other studies on terrestrial animals and fish (Hao et al, ; Ma, ; Zhang et al, ; Zhao, Qin, Sun, Zhang, & Wang, ). In turbot and crab studies, feeding dietary β‐conglycinin showed growth performance was significantly decreased.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, FE and PE were significantly decreased by 40–80 g/kg dietary β‐conglycinin. These findings were supported by the results in other studies on terrestrial animals and fish (Hao et al, ; Ma, ; Zhang et al, ; Zhao, Qin, Sun, Zhang, & Wang, ). In turbot and crab studies, feeding dietary β‐conglycinin showed growth performance was significantly decreased.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, to define mechanisms whereby excessive soybean induces growth depression in animals; this study investigated the role of purified soybean β-conglycinin, separating its effects from the effects of other anti-nutritional factors. Firstly, the present study observed that fish fed diet with β-conglycinin exhibited poor weight gain, which was also observed in piglets [7], [8] and rats [60]. However, survival was not influenced by the dietary treatments.…”
Section: Discussionmentioning
confidence: 50%
“…Among these anti-nutrients, β-conglycinin was suggested as being one of the key anti-nutritional factors [6]. A recent study has reported that β-conglycinin reduced weight gain in pigs [7]. However, little attention has been given to the potential negative effects of β-conglycinin on the growth, digestive and absorptive ability of fish.…”
Section: Introductionmentioning
confidence: 99%
“…Transient hypersensitivity to soybean antigens could lead to villus atrophy, crypt hypertrophy [1416,39]. In addition, β-conglycinin may accelerate the enterocyte apoptosis and the relative enterocyte migration rate for piglets in our previous study [18]. The above literature provides evidence that β-conglycinin could induce the low enterocyte activity.…”
Section: Discussionmentioning
confidence: 99%
“…Soybean allergies usually cause inflammatory disorders in the small intestine, characterized by villous atrophy and hyperplasia in the crypt, as well as accelerated enterocyte proliferation, apoptosis and migration [1418]. However, so far, there have been few studies into the effects of β-conglycinin on the intestinal barrier permeability of piglets.…”
Section: Introductionmentioning
confidence: 99%